2008
DOI: 10.1378/chest.07-0914
|View full text |Cite
|
Sign up to set email alerts
|

Improving Handoff Communications in Critical Care*: Utilizing Simulation-Based Training Toward Process Improvement in Managing Patient Risk

Abstract: Simulation-based training can be incorporated into the risk management process and can contribute to patient safety practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 23 publications
0
67
0
4
Order By: Relevance
“…The first category -handover content -has been mostly descriptive, concentrating on the completeness and accuracy of information (Arora et al 2005, Berkenstadt et al 2008, Horwitz et al 2009a. These studies typically showed verbal handover to be incomplete compared with the information available in the patient's record (Lamond 2000, Arora et al 2007 or compared with a pre-defined handover protocol (Catchpole et al 2007).…”
Section: Assessing Handover Qualitymentioning
confidence: 99%
“…The first category -handover content -has been mostly descriptive, concentrating on the completeness and accuracy of information (Arora et al 2005, Berkenstadt et al 2008, Horwitz et al 2009a. These studies typically showed verbal handover to be incomplete compared with the information available in the patient's record (Lamond 2000, Arora et al 2007 or compared with a pre-defined handover protocol (Catchpole et al 2007).…”
Section: Assessing Handover Qualitymentioning
confidence: 99%
“…Other single-site studies have shown standardized physician handoffs decrease "per-patient" handoff time, decrease handoff-related missed/inaccurate information, and improve communication. 10,11 With these few exceptions, however, studies linking standardized handoff processes to decreased patient harm are rare, and limited multicenter and pediatric research has been performed.…”
mentioning
confidence: 99%
“…The development of the instrument for peer evaluation of handoffs was informed by reviewing published handoff best practices 7,8,21 and handoff assessment instruments 22,23 as well as the six ACGME core competencies, particularly those requiring peer evaluations (communication, professionalism and systems-based practice) 9 for internal medicine residency programs. The institution's patient safety experts, residency program leadership and housestaff reviewed the instrument for content validity.…”
Section: Development Of the Peer Evaluation Instrumentmentioning
confidence: 99%
“…5 Best handoff communication practices have been published 6,7 and medical educators are developing innovative curricula to teach and evaluate handoff skills. 6,[8][9][10][11][12][13][14] The ability to capture handoff errors is limited by common barriers to safety reporting. 15,16 Additionally, since post-graduate year 1 (PGY1) trainees and post-graduate year 2-3 (PGY2-3) trainees typically handoff or "sign-out" to their peers, traditional evaluations by supervisors may be inadequate for assessing handoff skills.…”
Section: Introductionmentioning
confidence: 99%